Determinants of Financial Leverage: An Empirical Analysis of Manufacturing Companies in India - Eldhose, K. V.; Santhosh Kumar, S. (Indian Journal of Finance, 2019)
The paper attempted to examine the determinants of financial leverage of manufacturing companies in India. The financial data of 39 large cap companies listed in National Stock Exchange for a period of 14 years from 2004 to 2017 were used for analysis. The panel data results indicated that out of the seven selected companies' level determinants, all were significantly influencing financial leverage, except dividend payouts. While profitability, size of the firm, and cost of borrowing negatively influenced financial leverage, the other three significant determinants such as tangibility, liquidity, and growth positively influenced leverage. We concluded that capital structure decision of manufacturing companies in India was consistent with the hypothesis of pecking order theory rather than the trade-off theory.